2011
DOI: 10.2989/16073614.2011.633366
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of students’ negotiation of language, literacy and identity

Abstract: IntroductionThis article is based on a longitudinal, qualitative case study (2002 to 2004) of 20 Social Science students at a historically 'white',1 English-medium, South African university. The participants in our study are all from disadvantaged educational backgrounds and/ or are speakers of English as a second language.2 They were (with the exception of one student) the first in their families, sometimes the first in their communities, to attend university. The project tracked their shifts in language and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 19 publications
2
23
0
Order By: Relevance
“…These choice are often fluid, at times ambivalent, and 'alternate back and forward all the time' (Kapp & Bangeni, 2011: 204). Kapp and Bangeni (2011) have also recorded incidents where English is 'Afranised' to signal a specific township identity. Recent studies in South Africa have also recorded instances of learners expressing appreciation of their indigenous languages (e.g., Dyers, 2007;McKinney, 2007;Rudwick, 2008).…”
Section: Community Engagement As a Critical Factor In Language Planningmentioning
confidence: 99%
See 1 more Smart Citation
“…These choice are often fluid, at times ambivalent, and 'alternate back and forward all the time' (Kapp & Bangeni, 2011: 204). Kapp and Bangeni (2011) have also recorded incidents where English is 'Afranised' to signal a specific township identity. Recent studies in South Africa have also recorded instances of learners expressing appreciation of their indigenous languages (e.g., Dyers, 2007;McKinney, 2007;Rudwick, 2008).…”
Section: Community Engagement As a Critical Factor In Language Planningmentioning
confidence: 99%
“…Recent studies in South Africa have also recorded instances of learners expressing appreciation of their indigenous languages (e.g., Dyers, 2007;McKinney, 2007;Rudwick, 2008). Sometimes, learners may even risk derision and humiliation from their peers if they publicly assert their preference for English rather than their own language (Kapp, 2004;Kapp & Bangeni, 2011).…”
Section: Community Engagement As a Critical Factor In Language Planningmentioning
confidence: 99%
“…Such an approach that goes beyond the course of instruction and examines sociolinguistic issues is quite common. Kapp and Bangeni (2011) note that other studies conducted among students from disadvantaged backgrounds have indicated that 'becoming proficient in academic literacy is intimately connected to identity ' (197). However, they assert (Kapp and Bangeni 2011) that the shortcoming of previous studies in this field is that they have concentrated on first-year students.…”
Section: Introductionmentioning
confidence: 98%
“…3. A number of these intricate links between identity projects and studies in the Social Sciences are traced by Kapp and Bangeni (2011). 4.…”
Section: Notesmentioning
confidence: 99%